Investigating student's second language writing anxiety : a case study - Sabariah Abd. Rahim; Kasma Mohd Hayas (2014)
Anxiety is one of the essential factors in second language learning. It plays an important role in determining students' performance in the target language, be it positive or negative. Feeling nervous, uncertain or worry while engaging in a target language may cuse students to perform poorly in class, and this normally results in getting poor grades in their examination : and this is what students normally experience in writing class. In relation to this , the paper aims to investigate the relationship between students's anxiety in witing essay tasks in English and their choice to do the writing tasks, and also, the effects of this anxiety to their choice to do writing tasks in English. A group of students doing Level 3 Reading and writing in English in Universiti Malaysia Sabah were asked to answer Second Language Writing Anxiety Inventory (SLWAI) that elicited their second language writing anxiety and its relation to student's choice.